2017
DOI: 10.1038/s41598-017-01865-3
|View full text |Cite
|
Sign up to set email alerts
|

Indirect meta-analysis comparing clinical outcomes of total cervical disc replacements with fusions for cervical degenerative disc disease

Abstract: Anterior cervical discectomy and fusion (ACDF) and total cervical disc replacement (TDR) are considered effective treatments for patients with cervical degenerative disc disease (CDDD). An indirect meta-analysis including 19 randomized controlled trials (5343 patients) was conducted to compare the clinical outcomes of ACDF with TDR. Primary outcomes including functional indicators (NDI [neck disability index] score, neurological success and patient satisfaction), secondary outcomes including surgical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
(139 reference statements)
1
7
0
Order By: Relevance
“…Compared with ACDF, CDA had fewer secondary surgeries at the adjacent level in our meta‐analysis, which concurred with the findings of Xu et al . Although the definite risk factor for secondary surgery is still controversial, some studies indicate a relationship between the occurrence of adjacent segment degeneration and secondary surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with ACDF, CDA had fewer secondary surgeries at the adjacent level in our meta‐analysis, which concurred with the findings of Xu et al . Although the definite risk factor for secondary surgery is still controversial, some studies indicate a relationship between the occurrence of adjacent segment degeneration and secondary surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Xu et al provided what they termed an "indirect" meta-analysis using data from 5343 patients in which they estimated the relative effectiveness of each type of 4 different CDA and ACDF procedures, and these authors concluded that any of the total cervical replacement devices were good choices for improving functional outcomes and reducing secondary surgeries in comparison to ACDF. 36 One meta-analysis compared outcomes for patients undergoing single-level versus multilevel TDR and found the outcomes were equally favorable, 39 as did a recent individual study. 2 Similar to the current study, clinical trials of other cervical prostheses have also found that outcomes after two-level CDA were superior to outcomes after twolevel ACDF, including in patients with follow-up through 7 years.…”
Section: Discussionmentioning
confidence: 97%
“…Recent meta-analyses that compare CDA to ACDF are based on the large amount of published clinical trial data now available, although few focus specifically on two-level studies. 14,[34][35][36]38 One meta-analysis included 19 randomized controlled trials involving 4516 cases, the majority single level, with short-and midterm follow-up, and demonstrated better outcomes for CDA than ACDF on a wide variety of measures. 38 A number of other more recent meta-analyses have reported advantages to CDA.…”
Section: Discussionmentioning
confidence: 99%
“…Dejaegher et al reported in a 10-year follow-up after implantation of another cervical disc prosthesis 186 adverse events recorded for 73 patients, out of 89 included in the study, and 2% rate of reoperation at the index level. It has become common with recent publications to report that CTDRs have significantly lower rates of adverse events and reoperations than ACDF [3,11,13,32].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of arthroplasty devices have been developed [7,10]. Previous published studies have established that CTDR provides pain relief and functional improvements similar or superior to those of ACDF with lower rates of adjacent segment degeneration [11][12][13].…”
Section: Introductionmentioning
confidence: 99%